2012
DOI: 10.2478/v10325-012-0009-5
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Considerations and Recovery in Low Back Pain: Williams vs McKenzie

Abstract: Low back pain (LBP) is one of the most common muskuloscheletal disorders. It is associated with high costs in medical assistance and indirect losses through temporary work incapacity. Therefore, it represents a challenge for medical practice.There are many types of treatments and recommendations depending on doctors' knowledge and opinions, but two protocols stand out due to their -popularity‖: the Williams and McKenzie protocols. Given the duration of flares and relapses rate, it is important to apply an effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 3 publications
0
14
0
2
Order By: Relevance
“…Mckenzie exercise was one of back exercises proven could changing posture and decrease of musculoskeletal disorders, also increasing mobility of spine while work. Meanwhile, operationally, aims of give this exercise were to stretch back muscle (extensor muscle) and this exercise prioritize extension movement to have strength and stretch muscle along extensor and lumbosacral joint, resulting reduce of pain (Moldovan, 2012). Stretching muscle to resting length and had circulation optimal to the brain made this condition decrease of work fatigue.…”
Section: Resultsmentioning
confidence: 99%
“…Mckenzie exercise was one of back exercises proven could changing posture and decrease of musculoskeletal disorders, also increasing mobility of spine while work. Meanwhile, operationally, aims of give this exercise were to stretch back muscle (extensor muscle) and this exercise prioritize extension movement to have strength and stretch muscle along extensor and lumbosacral joint, resulting reduce of pain (Moldovan, 2012). Stretching muscle to resting length and had circulation optimal to the brain made this condition decrease of work fatigue.…”
Section: Resultsmentioning
confidence: 99%
“…In order to use the most effective type of motor exercise, studies have shown that Mackenzie extension exercises could be effective in relieving pain, improving lumbar spine mobility, accelerating the return to daily activity, and minimizing referrals to medical centers and the number of treatment sessions for patients. Williams et al also reported that lumbar lordosis was improved by using flexion exercises which had a significant effect on increasing the strength and endurance of the abdominal muscles, as well as reducing lumbar pain (5). On the one hand, researchers showed that more than 90% of patients improved after 6 months of participating in hydrotherapy program, and according to this report, hydrotherapy is an efficient treatment for patients with low back pain (6).…”
Section: Introductionmentioning
confidence: 89%
“…Combined Stretching -Core Stability Exercises. These exercises include two parts: core stability exercises for strengthening the abdominal weak muscles and stretching exercises for eliminating muscle shortness in the lumbar and pelvic sets as follows (5):…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The smooth circulation of the blood can be followed by reduced muscle spasm, which relaxes the muscles and activates the release of the endorphin system in the blood which results in less pain. This is reinforced by Moldovan (2013), which states that McKenzie Exercise is more effective than Williams Flexion in reducing low back pain. This is because the principle of McKenzie's exercise is to improve posture to reduce lumbar hyperlordosis.…”
Section: Funnel Plotmentioning
confidence: 99%